2016
DOI: 10.1590/0104-530x2625-15
|View full text |Cite
|
Sign up to set email alerts
|

Uma metodologia baseada no modelo SCOR® e em inferência fuzzy para apoiar a avaliação de desempenho de fornecedores

Abstract: Resumo: Na literatura acadêmica, tanto a seleção quanto a avaliação para o desenvolvimento de fornecedores vêm sendo abordadas como um problema de tomada de decisão no qual um conjunto de fornecedores é avaliado com base em múltiplos critérios de desempenho. Embora já existam centenas de metodologias quantitativas voltadasAbstract: In the academic literature, supplier selection and evaluation have been addressed as a decision-making problem in which a set of suppliers is assessed based on multiple criteria. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(61 reference statements)
1
4
0
1
Order By: Relevance
“…The results of the pilot application are somewhat similar to those found by the studies proposed by Lima Junior and Carpinetti [2], Osiro et al [4], and Lima Junior et al [21]. These studies also applied models based on fuzzy logic to assess suppliers of automotive companies and concluded that the vast majority of suppliers presented satisfactory performance, while a few suppliers required development programs and only one should be replaced.…”
Section: Discussion Of Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the pilot application are somewhat similar to those found by the studies proposed by Lima Junior and Carpinetti [2], Osiro et al [4], and Lima Junior et al [21]. These studies also applied models based on fuzzy logic to assess suppliers of automotive companies and concluded that the vast majority of suppliers presented satisfactory performance, while a few suppliers required development programs and only one should be replaced.…”
Section: Discussion Of Resultssupporting
confidence: 82%
“…When compared to other previous models to supplier performance evaluation, the proposed model has advantages such as: i. Unlike all the previous models found in literature [2][3][4][5]11,12,[17][18][19]21], it allows the decision makers to use linguistic expressions, or more than one linguistic term simultaneously, to evaluate the performance of a supplier in a given criterion; ii. Another advantage is dealt with group decision-making employing aggregation of the subjective judgments of several decision makers.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This shows that the interest in analyzing costs through a process perspective in the international community has increased recently. However, only one publication from South America [69], and two from Oceania (one in collaboration with researchers from a European country) [5], [17] have been selected during this review, highlighting the need to further promote cost-aware research through a process perspective in these continents.…”
Section: Discussionmentioning
confidence: 99%
“…References Publications Annotate costs using a cost model [3], [5], [6], [12], [13], [17], [23], [25], [27], [28], [31], [40]- [42], [46], [48], [49], [51], [53], [56], [59], [61], [63], [67], [71] 25 (37%) Propose performance indicators [20], [32], [34]- [36], [45], [50], [52], [54], [58], [65], [69], [72], [74]- [78] 18 (26%)…”
Section: Categorymentioning
confidence: 99%
“…Usually, the models express linguistic terms via triangular (or other) fuzzy numbers, and Likert scales are assumed to be equidistant, see e.g. Carrasco et al (2012), Casola et al (2005), Holeček and Talašová (2010), Lima et al (2016), Lin and Yeh (2012), or Yan et al (2017). However, if individuals do not perceive Likert scales to be equidistant, this input assumption might lead to unwanted distortion of results.…”
Section: Introductionmentioning
confidence: 99%